PEWARISAN KARAKTER KETAHANAN TERHADAP CHIVMV (CHILLI VEINAL MOTTLE VIRUS) PADA TANAMAN CABAI - Zahratul Millah; Sriani Sujiprihati; Sri Hendrastuti Hidayat (Jurnal Agroekoteknologi, 2012)
Inheritance of resistance trait to ChiVMV was studied in intraspecific capsicum population derived from a cross between two Capsicum annuum line, PBC495 as a resistance line and ICPN12#4 as a susceptible line. The resistance was assessed by diseased index (DI) and score of absorbance value at  405 nm, two weeks after inoculation. Based on t-test of F1 and F1R, it was concluded that there was no maternal effect. Nil symptoms resembling the resistant parent were identified in the progeny F2, BC1P1 (BC1 to the resistant parent) and BC1P2 (BC1 to the susceptible parent) populations. Segregation of resistance (nil DI and lower absorbance value) and susceptibility in the F2 fitted a 3:1 Mendelian ratio, indicating that resistance were controlled by a single dominant nuclear gene. Nil segregation of the trait in the test crosses in BC1P1 and a 1:1 ratio segregation in BC1P2 also confirmed the 3:1 gene segregating model as found in the F2. Heritability values of the trait were medium to high.Key words : inheritance, resistance, ChiVMV, pepper